Enhancing the Transformation of Electrical Engineering Learning in Vocational High Schools through WOKWI Web Simulation Training in Greater Bandung - Pramudita, Resa; Haritman, Erik; Rizqulloh, Muhammad Adli; Hartopo, Ibnu; Purnama, Wawan; Pawinanto, Roer Eka; Iglesias, Andre Reyvaldo (Institut Teknologi Nasional, Bandung, 2026)
This article reports a community service program designed to address persistent constraints in Technical and Vocational Education and Training (TVET) microcontroller and IoT practicum, including limited laboratory kits, maintenance costs, and uneven access to hardware that can reduce the frequency and quality of hands-on learning. To support project-based learning and the ongoing digital transformation of electrical engineering education, the program aimed to enhance vocational electrical teachers’ competence in using a web-based simulation platform for ESP32-oriented microcontroller and IoT instruction. A one-day, hands-on workshop was developed using the GOAD (Goal–Objectives–Activities–Deliverables) framework and implemented with twenty teachers from ten vocational high schools. Activities included an introduction to WOKWI, basic C programming, microcontroller and IoT concepts, and contextual case studies such as automatic systems and flood-detection projects. Evaluation data were collected through a 12-item Likert questionnaire covering content, delivery, and practice aspects. Results showed high satisfaction, with average scores of 83.5% for content, 81.75% for delivery, and 79.25% for hands-on practice. The program indicates that WOKWI is a feasible tool to mitigate laboratory constraints and to support scalable, low-cost, and interactive IoT practicum in TVET.